REVIEW: PROTEIN INTAKE DURING BREASTFEEDING, COMPLEMENTARY AND PRE-SCHOOL PERIODS - Alzaheb, Riyadh A.; Almatari, Mohammad; Alloubani, AlaDeen; Alatawi, Noorah; Alatawi, Naiemah (European Scientific Journal, ESJ, 2015)
Background: In recent years, research in the field of nutrition has broadened from how best to meet nutritional needs and prevent deficiencies to encompassing the impact nutrition has on health in the longer term. Consequently, a convincing body of evidence has been established which demonstrates that the nutrition experienced early in life (a period that is vital in physiological development) is likely to have a long-term impact on a personâ€™s health. Purpose: This review investigated the impact of different levels of protein intake concerning three specific periods of early life: the breastfeeding period, the complementary feeding period and the pre-school period. Methodology: In searching for applicable articles, the search has been done using PubMed and MedLine searching engines and were limited to search peer-reviewed journals only, both were used to set specific criteria. Also, the basic Boolean search operator â€œANDâ€ was used to narrow down search results as additional parameters. The citation index searching technique was also used to inspect the citation frequency of authorâ€™s work in other publications. Nutrition, Breastfeeding, complementary feeding and preschool period, all these keywords were used in the search. Findings: A growing number of studies are exploring the potential effects of a high protein intake early in life on growth and obesity risk. These studies cover a wide range of ages, from breastfeeding through to complementary feeding and then on to the pre-school period. Some these studies suggest that a higher level of protein intake during infancy and early childhood is associated with more rapid growth and a higher body mass index (BMI) in later childhood. Conclusion: The age period that is the most sensitive to high protein intake remains unclear, and there is limited information on the effects of different types of protein.These findings are of interest; the role of protein intake in the development of overweight and obesity requires further study.